Letters to Kate : life after life - Klaus, Carl H. (Sightline books., 2006)
Sorrow is "not a state but a process" that needs "not a map but a history. ... There is something new to be chronicled every day," writes C.S. Lewis in A Grief Observed. When Carl Klaus's wife of thirty-five years died suddenly from a cerebral hemorrhage, right before Thanksgiving in 2002, he took the only road toward recovery that made sense to him: he started writing letters to her, producing a unique history of grief, solace, and love. His vivid and thoughtful letters will resonate with everyone whose loss confronts them with emotional, psychological, and philosophical questions for whic